Consumo de Mídias e Juventudes: Usos e repertórios midiáticos dos jovens sul-mato-grossenses - JÚLIA VERENA PEREIRA DA SILVA (2024)
ABSTRACT The production, consumption and circulation models of mass media have undergone various transformations, especially in recent decades. In addition to socio-cultural and economic changes, alterations in the patterns of supply and access to these media in contemporary societies have also been influenced by the digitalization of information and the use of the internet as a means of communication. In this context, this research aims to analyze media consumption among youth, focusing on the study of media repertoires of youth aged 16 to 24, from Mato Grosso do Sul, Brazil. Emphasis was placed on the uses and how individuals consume and appropriate various media products and technologies, considering the selective exposure to the media. The general objective was to examine how the media practices and preferences of young people are related to their daily routines and perceptions of usage. It is assumed that the audience selects and organizes media products and content according to their resources and those available in their social environment, based on their expectations and daily practices. The research adopted a mixed methods methodology, combining quantitative and qualitative data into a single study. The quantitative stage (T1) involved the analysis of 2,207 questionnaires administered in 2019, in both public and private high schools and universities in Campo Grande (MS). The qualitative stage (T2) consisted of five focus group interviews conducted in 2022, involving 41 participants from the same age group. The results identified the smartphone/mobile phone as the central device in the communicative practices of the young participants. The analysis of usage perceptions also revealed the centrality of expressions such as adaptability, flexibility, and versatility in the media choices of young people. The participants' understanding that media can be used adaptably and flexibly to perform multiple roles in their daily lives supports the assumption presented by the research. It is concluded that the concept of media repertoires proved to be important for analyzing the relationship between media consumption and youth, serving as a starting point for understanding how perceptions and motivations for media usage are expressed in the media repertoires of young people. Keywords: Communication; Media consumption; Media repertoires; Youth; Social media uses.